Effect of filler and blending with SBR and NR on thermally induced crystallization of high-cis BR as evaluated by dynamic mechanical analysis - M. Wunde; M. Klueppel (eXPRESS Polymer Letters)
The effect of thermally induced crystallization of high-cis polybutadiene (BR) on dynamic mechanical spectra is analyzed under different heating and cooling conditions. It is studied how the addition of carbon black and the blending with styrene-butadiene rubber (SBR) and natural rubber (NR) is affecting the crystallization. For unfilled BR an increased heating rate after fast cooling delivers less crystallization demonstrating that crystal formation requires time. With rising carbon black (CB) loading, a pronounced increase of crystallization speed is found indicating that CB supports nucleation and growth of BR crystals. In BR/SBR blends, which are detected as a single phase in dynamic mechanical spectra, crystallization is reduced for low SBR amounts and seems to disappear totally for 50/50 blends. In blends of BR, SBR, and NR the filler distribution is determined by comparing the peak heights in the loss modulus G″ of unfilled and filled compounds. The filler located in each phase is determined from the increase of the peak height corresponding to the respective phase. It is found that the filler is mainly located in the NR phase.